2006
DOI: 10.1111/j.1365-2257.2006.00785.x
|View full text |Cite
|
Sign up to set email alerts
|

Cryoprecipitate production: the use of additives to enhance the yield

Abstract: Cryoprecipitate is still widely used to treat hemophilia A in developing countries. However, the yield of factor VIII is relatively low averaging, i.e. only 50%. We have attempted to enhance the yield by adding sodium citrate to the plasma following the method of Shanbrom and Owens (Blood 98, 2001, 60a). Fresh-frozen plasma (FFP) units were processed either as control plasma or after the addition of 10% sodium citrate. Cryoprecipitate was produced from both. After resuspension, calcium chloride was added to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Numerous previous studies have demonstrated that these minimum levels are achievable when the starting product is FFP, 14‐18 although reduction in the recovery of some factors occurred when certain pathogen inactivation techniques were attempted 17,18 . To improve the yield of VIIIC, collecting the plasma destined for cryo production in heparin instead of citrate has been shown to be efficacious, 19 and using large quantities of sodium citrate has likewise been demonstrated to increase the recovery of both VIIIC and fibrinogen, 16,20 although the results seem to be variable 16 . As blood centers in North America are now avoiding the manufacture of plasma products from female donors due to the risk of TRALI from HLA antibodies, sufficient inventories of FFP may become jeopardized.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous previous studies have demonstrated that these minimum levels are achievable when the starting product is FFP, 14‐18 although reduction in the recovery of some factors occurred when certain pathogen inactivation techniques were attempted 17,18 . To improve the yield of VIIIC, collecting the plasma destined for cryo production in heparin instead of citrate has been shown to be efficacious, 19 and using large quantities of sodium citrate has likewise been demonstrated to increase the recovery of both VIIIC and fibrinogen, 16,20 although the results seem to be variable 16 . As blood centers in North America are now avoiding the manufacture of plasma products from female donors due to the risk of TRALI from HLA antibodies, sufficient inventories of FFP may become jeopardized.…”
Section: Discussionmentioning
confidence: 99%
“…The recovery of about 50% FVIII activity is comparable with the obtained from cryoprecipitates (Yousef et al 2006). All plasma-derived FVIII concentrates produced currently are purified from cryoprecipitate, which isolation requires refrigerated continuous centrifuges (Burnouf 2007).…”
Section: Resultsmentioning
confidence: 79%
“…Cryoprecipitate is prepared by slowly thawing fresh frozen plasma resulting in the formation of precipitate that can be resuspended in plasma and stored. Attempts have been made to improve the yield of factor VIII and fibrinogen to meet the requirements of the American Association of Blood Banks for blood products (17)(18)(19)(20).…”
Section: Key Pointsmentioning
confidence: 99%